Art education and visual culture: everydaylife as artisticpractice (Revista Apotheke, 2023)
The present study brings as a reflection the everyday life in art teaching and visual culture as an epistemic construction. To do so, we highlighted some authors that were added to this corpus, to provoke crossings in the subjective relations of the subjects with the ordinary practices, such as: Michel de Certeau (2014), Suely Rolnik (2019), Gilles Deleuze (2022), Nilda Alves (2001), María Acaso (2011), among others. Furthermore, we problematize the implications of being a teacher-artist on the pedagogical frontier with practices of the self, taking the series 1 a day and the Poetic Medications & Artistic Prescription as objects of investigation. Such practices elaborate strategies of resistance to the dictates of the capitalist system, in an attempt to create alternative paths for what has already been established as art education.
Keywords: everyday; artistic practices; art education; visual culture